Racial and Ethnic Disparities in Kidney Transplant Access Within a Theoretical Context of Medical Eligibility. Issue 7 (July 2020) - Ku, Elaine; Lee, Brian K.; McCulloch, Charles E.; Roll, Garrett R.; Grimes, Barbara; Adey, Deborah; Johansen, Kirsten L.
Abstract : Background: Non-Hispanic black (NHB) and Hispanic patients have lower access to kidney transplantation compared to non-Hispanic whites (NHWs). We examined whether differences in the prevalence of comorbidities that affect eligibility for transplant contribute to disparities in receipt of transplantation. Methods: We performed a retrospective study of 986 019 adults who started dialysis between 2005 and 2014, according to the United States Renal Data System. We compared prevalence of comorbidities that could influence transplant eligibility by race/ethnicity. We examined time to first transplant by race/ethnicity in this overall cohort and in a very healthy sub-cohort without conditions that could be contraindications to transplantation. Results: During 2.3 years of mean follow-up, 64 892 transplants occurred. NHBs and Hispanics had a lower prevalence of medical barriers to transplantation at the time of dialysis initiation than NHWs, including age >70 years (26% in NHB versus 47% in NHW) and malignancy (4% in Hispanics versus 10% in NHWs). Access to transplant was 65% lower (95% CI, 0.33–0.37) in NHBs and 43% lower (95% CI, 0.54–0.62) in Hispanics (versus NHWs) in the first year after end-stage renal disease, but by Year 4, access to transplantation was not statistically significantly different between Hispanics or NHBs (versus NHWs). In our very healthy cohort, racial and ethnic disparities in access to transplantation persisted up to Year 5 in NHBs and Year 4 in Hispanics after end-stage renal disease onset. Conclusions: Differences in medical eligibility do not appear to explain racial/ethnic disparities in receipt of kidney transplantation and may mask the actual magnitude of the inequities that are present. Abstract : Supplemental Digital Content is available in the text.